A profile of the Manila and Quezon City public secondary social studies supervisors, department heads its implications for supervision of social studies education in Thailand - Pruksatien, Somruan 1948-
This study describes the characteristics, duties and responsibilities of, and problems met by all the public secondary social studies supervisors and department heads in SY 1973-1974. The supervisors and department heads are predominantly women, of whom there were more single than married in Manila and more married than single in Quezon City. Twelve percent from Manila and 6 from Quezon City have acquired their Master's Degree or its equivalent. They all have the minimum civil service eligibility and perform three main supervisory functions: inservice training, curriculum development, research and evaluation. This likewise includes the study of the problems and difficulties they have met and the corresponding solutions they have suggested.